The endocrine response to exercise and training in young athletes - Eliakim, A.; Nemet, D. (Pediatric Exercise Science, 2013)
The manuscript "Plasma Somatomedin-C in 8- to 10-Year-Old Swimmers" by Denison and Ben-Ezra published in the first issue of Pediatric Exercise Science in 1989 was among the first to address the relationship between growth, the growth hormone (GH)/insulin like growth factor-1 (IGF-1) axis, and exercise. Since their pioneering article, this topic has become of great interest to pediatricians and pediatric exercise researchers, and today our understanding of the effects of exercise training on the growth axis during childhood and puberty, on differences between systemic and local (i.e., muscle) responses to exercise, and our ability to use these responses to assist the adolescent competitive athlete in the evaluation of the training load have markedly improved. The aim of the present review is to summarize our current knowledge on this topic.